Provider Perspectives on the Feasibility and Utility of Routine Patient‐Reported Outcomes Assessment in Heart Failure: A Qualitative Analysis. Issue 2 (21st January 2020) - Wohlfahrt, Peter; Zickmund, Susan L.; Slager, Stacey; Allen, Larry A.; Nicolau, Jose Nativi; Kfoury, Abdallah G.; Felker, G. Michael; Conte, Jorge; Flint, Kelsey; DeVore, Adam D.; Selzman, Craig H.; Hess, Rachel; et al.
Abstract : Background: Patient‐reported outcomes (PROs) objectively measure health‐related quality of life and provide prognostic information. Advances in technology now allow for rapid, patient‐friendly PRO assessment and scoring, yet the adoption of PROs in clinic has been slow. We conducted a multicenter qualitative study of diverse providers to describe the barriers and facilitators of routine PRO use in heart failure clinics. Methods and Results: Sixty heart failure providers from 5 institutions participated in 8 focus groups to explore provider perspectives on the use of heart failure‐specific and generic PROs in clinical practice. A qualitative editing approach was used to analyze the data, whereby a coding dictionary was iteratively developed and applied using the qualitative software program Altas.ti. Three main themes, supporting and impeding PRO use, emerged: (1) data collection; (2) presentation and interpretation; and (3) utility and value. For each construct, we identified perspectives that highlighted both barriers and facilitators. Providers identified burden, survey fatigue, and language/health literacy barriers as potentially impeding data collection. Optimal workflow, PRO frequency and length, use of PRO translations, and assistance of a patient's proxy were suggested as facilitators. Focus group discussions provided insight on how to display PROs to support its interpretability and sharing. Furthermore, the need to educate providers on the utility and value PROs over and above current clinical approaches emerged. Conclusions: Overcoming the barriers and supporting facilitators of PRO adoption could potentially lead to more successful adoption of PROs in heart failure clinics.